Improved link repair technique for multicast routing in Wireless Mesh Network - Anwar, Farhat; Azad, Md. Saiful; Rahman, Md. Arafatur; Bari, S.M. Sadakatul; Masud, Muhammad Mehdi (2011)
Efficient multicasting over Wireless Mesh Network (WMN) is challenging due to dynamic and multi-hop wireless communication among multicast group members. Multicast Ad hoc On-Demand Distance Vector (MAODV) protocol is a tree based multicast routing protocol that enables dynamic, self-starting, multi-hop routing between participating mobile nodes wishing to join or participate in a multicast group in Wireless Mesh Network (WMN). The mobility of mobile nodes often causes link breakage in the tree-based protocols which sometime results in tree partitioning and poor performance. In MAODV, when a broken link is detected between two nodes on the multicast tree, the node downstream to the break is responsible for initiating the repair of the broken link. After link repair, it is likely that the previous distance between the nodes (nodes downstream to the link breakage) and the group leader will not remain same. The shortest path from the group leader to the nodes downstream to the node which initiates link breakage is not ensured. Moreover, if the node attempting to repair a tree link break does not receive a response after certain attempts, it assumes that the multicast tree is not repairable currently and this leads to tree partitioning. In this paper, an improved link repair technique is proposed which ensures shortest path from any node to the group leader. Simulation results demonstrate significant improvement in performance metrics compared to standard MAODV.